Dampak Struktur Pasar terhadap Daya Saing UMKM (Studi Kasus UMKM di Kota Jambi) - Rahma, Sri; Ferdiansyah, Ferdiansyah; Andesti, Olga; Andira, Pipi Dwi; Salsabila, Ilmi Aurelin (SCIENTIFIC JOURNAL OF REFLECTION : Economic, Accounting, Management and Business, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a vital role in Indonesia’s economy, yet their competitiveness remains constrained by structural market challenges. This study aims to analyze the impact of market structure on MSME competitiveness in Jambi City and to identify development strategies that align with internal and external business conditions. A mixed-methods approach was employed, combining quantitative surveys with 120 MSME respondents and qualitative interviews with stakeholders, including local government officials and business actors. SWOT analysis was used to map strengths, weaknesses, opportunities, and threats faced by MSMEs, while thematic analysis captured insights from in-depth interviews. The results indicate that MSMEs in Jambi are positioned in Quadrant I (aggressive), with high internal strengths (score: 4.00) and strong external opportunities (score: 4.00), surpassing weaknesses (2.66) and threats (2.67). These findings suggest that Jambi MSMEs have substantial capacity to grow through strategic action. Key strategies include product quality improvement, digital innovation, business management enhancement, and stronger marketing through STP (Segmentation, Targeting, and Positioning). Government support, digital literacy training, and collaborative networks are also critical to overcoming structural barriers such as limited market access and low technology adoption. This study contributes to understanding how market structure shapes MSME competitiveness and offers practical recommendations to improve their resilience and performance in a rapidly evolving economic environment.